Dry calving processes at the ice cliff of Strandline Glacier northern Victoria Land, Antarctica - Guglielmina Diolaiuti; Michele Motta; Claudio Smiraglia; Giorgio Vassena (Annals of Glaciology, 2004)
AbstractThis paper describes seasonal variations on Strandline Glacier, Terra Nova Bay, northern Victoria Land, Antarctica, obtained from measurements during two field campaigns (2000/01 and 2002/03). By applying different methodologies and techniques, it was possible to calculate summer changes in thickness (mean decrease over the whole glacier surface of 0.04 mw.e.) and in volume (decrease of 352 μ3 at the terminus). This serves to identify and quantify the processes responsible for these variations (e.g. melting, evaporation, wind erosion/deposition and calving) and to understand the energy transfers at the glacier–air interface. One particular feature of the glacier is the presence of an ice cliff at the terminus, which causes ablation owing to dry calving. This process brought about a summer retreat rate of 1 mweek–1 in the central part of the front during the study period. Qualitative observations carried out during previous field campaigns and quantitative analysis performed during the last two expeditions have provided an understanding of the mechanism underlying the ablation processes, thus confirming the available literature on this topic.